Fractal characteristics of a worn wall and the influence on the particle-wall collisions. (May 2022) - Zhang, Ri; Wu, Longqi; Wang, Xujie; Liu, Yong
Highlights: A new model is proposed to study the random rebound process of particles. The new model considers velocity attenuation and multiple collisions. Some classical collision models can be interpreted by the present theory. Abstract: A new particle-wall collision model is proposed to analyse the random rebound process of particles after collision with a rough wall. The new model includes two parts. First, the wear caused by particle collisions and the self-similarity of the wall microstructure are considered. The topography of a rough wall is constructed using fractal theory combined with an empirical erosion formula. Second, a return-to-subdivision method is used to determine the contact point between the particle and wall. The hard ball model is used to analyse the motion state of the rebound particles. The present model is numerically implemented through the Monte Carlo method and validated by comparison with the experimental data available in the literature. The possible reasons for the deviation between the predicted and measured results are presented. In addition, the compatibility of the present model with classical models is discussed in detail.